Avanços e desafios para a consolidaç\~ao dos serviços de acolhimento familiar para crianças e adolescentes no Brasil - Enid Rocha Andrade Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article evaluates the trajectory of foster family care services in Brazil, since its entry into the federal government's select public policy agenda, from the elaboration of the National Plan for Living in Family and Community (2006) which brought, among its objectives, the promotion and implementation of foster family programs, as an alternative to institutional care for children and adolescents. The analysis presents the path of reconfiguration of institutional (SAI - serviços de acolhimento institucional) and family care services, based on the rules and norms established in the period from 2010 to 2022, which aimed to encourage the reorganization of care services in the country, in accordance with the principles of Child and Adolescent Statute (ECA - Estatuto da Criança e do Adolescente). Throughout the article there are performance analyzes of some indicators that measure the quality of these services in the country. The analysis of the trajectory shows progress, but highlights the need to accelerate expansion throughout the national territory and improve the quality of these services in Brazil so that they become, in fact, an alternative to institutional care for children and adolescents in the country.
Keywords: B55; J13; L38; D02; 330; child and adolescent; foster family; public policies